Evaluation of the MiStent sustained sirolimus eluting biodegradable polymer coated stent for the treatment of coronary artery disease: does uniform sustained abluminal drug release result in earlier strut coverage and better safety profile?. (4th May 2017) - Tijssen, Ruben Y.G.; Kraak, Robin P.; Lu, Huangling; Mifek, Jeffrey G.; Carlyle, Wenda C.; Donohoe, Dennis J.; De Winter, Robbert J.; Koch, Karel T.; Wykrzykowska, Joanna J.
ABSTRACT: Introduction : Treatment of coronary artery disease has made strides over the last decades. Development of drug eluting stents (DES), coated with a polymer layer and an anti-proliferative drug to reduce neointimal hyperplasia, has reduced the incidence of in-stent-restenosis relative to treatment with bare metal stents. Patients treated with first generation DES more likely suffer from (very) late events which can be cause by the permanent presence of a polymer. Therefore second generation DES with more biocompatible coatings, and third generation DES, with very thin struts coated with biodegradable polymers, were developed. Areas covered : The MiStent SES is one of these third generation DES and is designed to limit the duration of polymer exposure, optimize coronary vessel healing and more precisely and consistently control drug elution to improve safety and clinical outcomes. This review provides a detailed description of the technique behind the MiStent SES, and describes the pre-clinical and clinical trials conducted with this device to date. Expert commentary : Recent clinical trials have shown non-inferiority of very thin strut biodegradable polymer coated DES compared to durable polymer coated DES, whilst maintaining an excellent safety profile. Longer follow-up, to see the real potential benefits of these devices, is mandatory however.